Hubungan antara Skor GCS dengan Kadar C-Reactive Protein (CRP) Pasien Cedera Otak Traumatik di IGD RSUD Ulin Banjarmasin - Suharto, Gusti Muhammad Fuad; Sikumbang, Kenanga M; Pratiwi, Dewi I N (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2019)
AbstrakLatar Belakang dan Tujuan: Pada cedera otak traumatik (COT) terjadi perubahan tingkat kesadaran dan neurologis pasien, sehingga perlu dilakukan penilaian skor GCS untuk mengkategorikan tingkat keparahan COT. Saat terjadinya COT, akibat dari pengeluaran mediator inflamasi, hati akan mengeluarkan suatu penanda pertama inflamasi, yaitu c-reactive protein (CRP). Tujuan penelitian ini untuk mengetahui apakah terdapat hubungan antara skor GCS dengan kadar CRP pasien COT di IGD RSUD Ulin Banjarmasin.Subjek dan Metode:Penelitian ini menggunakan studi desain observasional analitik dengan rancangan potong lintang. Data diambil secara prospektif dengan metode consecutive sampling pada pasien COT yang masuk ke IGD RSUD Ulin Banjarmasin periode Juli-September 2018 yang memenuhi kriteria inklusi dan eksklusiHasil:Didapatkan 53 subjek terdiri dari 42 pasien laki-laki dan 11 pasien perempuan dengan distribusi 22 (41,5%) pasien COT ringan, 20 (37,7%) pasien COT sedang, dan 11 (20,8%) pasien COT berat. Pengukuran kadar CRP didapatkan rata-rata 4,64 mg/l pada COT ringan, 18,00 mg/l pada COT sedang, dan 26,73 mg/dl pada COT berat. Analisis data menggunakan uji Kruskal-Wallis dengan tingkat kepercayaan 95% menunjukan peningkatan kadar CRP seiring dengan semakin beratnya COT (p=0,034), analisis Post Hoc menggunakan Mann-Whitney Test didapatkan perbedaan bermakna peningkatan kadar CRP antara pasien COT sedang berat dibandingkan COT ringan.Simpulan: Terdapat hubungan antara skor GCS dengan kadar CRP pada pasien cedera otak traumatik.Correlations between GCS Score and C-Reactive Protein (CRP) in Patients with Traumatic Brain Injury at Emergency Departement of Ulin General Hospital BanjarmasinAbstractBackgound and Objective: In traumatic brain injury (TBI), the level of severity could be assessed by GCS, so it is necessary to measure the GCS score to categorize the severity of TBI. TBI may followed by inflammatory mediators cell and one of inflammation marker released by liver, namely c-reactive protein (CRP).The purpose of this study is to analyze correlation between GCS scores and CRP levels in patients with traumatic brain injury at the emergency departement of Ulin General Hospital Banjarmasin. Subject and Method: This study is a analytic observational study with cross sectional design. Data acquired prospectively with consecutive sampling method in TBI patients who entered the emergency department of Ulin General Hospital in the period from July-September 2018 that fulfilled inclusion criteria and exclusion criteria.Result: We obtained 53 subjects consisted of 42 males and 11 females with a distribution of 22 (41.5%) mild TBI patients, 20 (37.7%) modarate TBI patients, and 11 (20,8%) severe TBI patients. Measurements of CRP levels were obtained at an averange of 4.64 mg/l in mild TBI, 18.00 mg/l in moderate TBI, and 26.73 mg/l in severe TBI. There was correlation between the increasing of CRP levels with severity of TBI using Kruskal-Wallis test with a confidence level of 95% (p=0.034), in Post Hoc analysis using Mann-Whitney test, there was significant differences in elevated CRP levels between moderate-severe TBI patients compared to mild TBI patients. Conclusion: It was concluded that there was a corellation between GCS scores and CRP levels in TBI patients.